2023
DOI: 10.1007/s10071-023-01742-9
|View full text |Cite
|
Sign up to set email alerts
|

Appeasement function of displacement behaviours? Dogs’ behavioural displays exhibited towards threatening and neutral humans

Abstract: Appeasement signals are behavioural patterns displaying an animal’s non-aggressive attitude and are hypothesized to reduce the aggressive behaviours in the receiver. In domestic dogs, specific displacement behaviours (i.e., behavioural patterns exhibited without an apparent function related to the ongoing situation), have been suggested to function as appeasement signals. To test this possibility, we assessed whether the occurrence of these behaviours was dependent on a social conflict context, predicting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Thus, the use of naturalistic videos, including their auditory stimuli was adopted to expose dogs to a standardised conflict-ridden (threatening dog) and non-conflict-ridden (neutral dog) situation and measure the occurrence of displacement behaviours and facial expressions under the two conditions. Although in our previous study with human strangers [20], dogs were not observed to exhibit these behaviours more frequently in a threatening compared to a neutral condition, given the few studies carried out with conspecifics, the predictions for this study were based on the "appeasement signal hypothesis". Hence, it was predicted that dogs would exhibit displacement behaviours more frequently when exposed to videos of conspecifics showing threatening compared to neutral behaviour.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Thus, the use of naturalistic videos, including their auditory stimuli was adopted to expose dogs to a standardised conflict-ridden (threatening dog) and non-conflict-ridden (neutral dog) situation and measure the occurrence of displacement behaviours and facial expressions under the two conditions. Although in our previous study with human strangers [20], dogs were not observed to exhibit these behaviours more frequently in a threatening compared to a neutral condition, given the few studies carried out with conspecifics, the predictions for this study were based on the "appeasement signal hypothesis". Hence, it was predicted that dogs would exhibit displacement behaviours more frequently when exposed to videos of conspecifics showing threatening compared to neutral behaviour.…”
Section: Introductionmentioning
confidence: 70%
“…They found that lip licking was associated with an active submissive attitude in dogs (e.g., ears flattened, tail wagging, crouched posture, greeting behaviour), but was not displayed in highly threatening situations [21]. In a previous study conducted by our research team [20], the threatening approach test (TAT) was adopted to test the dogs' responsiveness to unfamiliar humans approaching them in either a threatening (bent posture and staring) or a neutral (relaxed posture, not staring at the dog) way. In general, the dogs' attitudes in both conditions could be categorised as either reactive or non-reactive (i.e., presence or absence of barking and lunging).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…originating from the throat and mouth 38 Not Whining Sound production ceases 38 Panting Increased shallow respiration through an open mouth, may have tongue out 47 Mouth not visible Can not see mouth area. Panting/Not Panting cannot be determined ( defined for this study ) Not Panting Mouth is closed—normal breathing resumes 38 Yawn An involuntary intake of breath through a wide-open mouth 38 Shake Dog's whole body and/or head starts moving rapidly from side to side while the dog stands 48 Bark Head and lips forward, mouth opening and shutting repeatedly to omit a large, sharp, short sound emitted from the throat 38 Howl Raised muzzle perpendicular to ground and emits a long, drawn-out sound through semi-closed jaws. Stops when dog lowers head and/or when sound is no longer produced ( modified ) 38 …”
Section: Methodsmentioning
confidence: 99%